2023
DOI: 10.3389/fimmu.2022.1044462
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to environmental air pollutants as a risk factor for primary Sjögren’s syndrome

Abstract: BackgroundEnvironmental etiology of primary Sjögren’s syndrome (pSS), an autoimmune disease, has been proposed. This study determined whether the exposure to air pollutants was an independent risk factor for pSS.MethodsParticipants were enrolled from a population-based cohort registry. Daily average concentrations of air pollutants from 2000 to 2011 were divided into 4 quartiles. Adjusted hazard ratios (aHRs) of pSS for exposure to air pollutants were estimated in a Cox proportional regression model adjusting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Studies have explored risk factors associated with autoimmune dry eye. [9] Many clinical randomized controlled trials have been reported, exploring many drugs and therapies for the treatment of autoimmune diseases. Intramuscular injection of ianalumab (VAY736), shown to be effective and safe [10] ; Autologous versus allogeneic versus umbilical cord sera has obvious effect on severe dry eye [11] ; LD-IL-2 was effective and well tolerated in patients with pSS, and it restored immune balance, with enhanced regulatory T cells and CD24highCD27 + B cells.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have explored risk factors associated with autoimmune dry eye. [9] Many clinical randomized controlled trials have been reported, exploring many drugs and therapies for the treatment of autoimmune diseases. Intramuscular injection of ianalumab (VAY736), shown to be effective and safe [10] ; Autologous versus allogeneic versus umbilical cord sera has obvious effect on severe dry eye [11] ; LD-IL-2 was effective and well tolerated in patients with pSS, and it restored immune balance, with enhanced regulatory T cells and CD24highCD27 + B cells.…”
Section: Resultsmentioning
confidence: 99%
“…Hitherto, the Epstein-Barr virus (EBV), cytomegalovirus (CMV), hepatitis C (HCV), Coxsackievirus and human Tlymphocyte virus type I (HTLV-1), mumps virus, hepatitis B and human parvovirus B19 have been reported [27][28][29]. The role of particulate pollutants in the development of SS has been examined in several studies, revealing that certain particulate pollutants can be recognized as antigens by airway epithelial cells and subsequently presented to immune cells [30]. Other environmental factors may also in uence pSS.…”
Section: Discussionmentioning
confidence: 99%
“…Personal determinants, closely connected to the local environment, are also involved in the pathogenesis of primary SjS (22). Evidence for the critical role of lifestyle and environmental factors is increasing, including a potential influence of diet (23,24), soil metals (25), seasonality (7), and air pollution (26). We recently reported that the significant variability in the presentation of systemic SjS is strongly linked with geoepidemiological personal determinants such as age, gender, ethnicity, and place of residence (27).…”
Section: Influence Of Extreme Climate On Systemic Diseasementioning
confidence: 99%